2021
DOI: 10.1038/s41598-021-84764-y
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise and aerobic fitness level do not modify motor learning

Abstract: Motor learning may be enhanced when a single session of aerobic exercise is performed immediately before or after motor skill practice. Most research to date has focused on aerobically trained (AT) individuals, but it is unknown if aerobically untrained (AU) individuals would equally benefit. We aimed to: (a) replicate previous studies and determine the effect of rest (REST) versus exercise (EXE) on motor skill retention, and (b) explore the effect of aerobic fitness level (AU, AT), assessed by peak oxygen upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…HIIT protocols may be better than moderate intensity protocols as they challenge the cardiovascular (ie, increased heart rate response) and metabolic system (ie, increased blood lactate post-exercise) to a greater extent and are likely to produce improvements in motor skill retention or other indices of neuroplasticity. [71][72][73] Three studies incorporated HIIT (ie, vigorous exercise) in this review, and preliminary findings suggest that a single session of HIIT can increase CME, improve motor learning and retention, and increase levels of circulating BDNF. While HIIT is promising in exercise priming studies, it is important to note that even in the high intensity interval regimens, stroke survivors may not reach their ventilatory thresholds, due to disease severity, age, and other comorbidities.…”
Section: Other Exercise Parametersmentioning
confidence: 99%
“…HIIT protocols may be better than moderate intensity protocols as they challenge the cardiovascular (ie, increased heart rate response) and metabolic system (ie, increased blood lactate post-exercise) to a greater extent and are likely to produce improvements in motor skill retention or other indices of neuroplasticity. [71][72][73] Three studies incorporated HIIT (ie, vigorous exercise) in this review, and preliminary findings suggest that a single session of HIIT can increase CME, improve motor learning and retention, and increase levels of circulating BDNF. While HIIT is promising in exercise priming studies, it is important to note that even in the high intensity interval regimens, stroke survivors may not reach their ventilatory thresholds, due to disease severity, age, and other comorbidities.…”
Section: Other Exercise Parametersmentioning
confidence: 99%
“…A recent meta-analysis examining the impact of exercise on motor learning conducted by Wanner et al (2020) suggests that stronger effects of exercise are noted when this intervention follows skilled motor practice, although recent work showed no effect of exercise on learning even when exercise follows motor practice 81 . Though other work shows that exercise preceding skilled motor practice enhanced motor learning, this past research only considered young healthy individuals and single sessions of practice 6,7,82 .…”
Section: Exercise and Motor Skill Learningmentioning
confidence: 99%
“…While some studies show that a single bout of acute cardiorespiratory exercise can improve motor performance and online learning [21][22][23] accumulating evidence indicates that exercise is particularly bene cial in enhancing the o ine consolidation of a new motor skill [24][25][26][27] . Although several studies have found no apparent bene t of acute exercise on motor consolidation [28][29][30][31] , a recent meta-analysis suggests this may be explained by variations in motor learning task and exercise characteristics Exercise intensity appears to be of particular importance, with greater bene ts following high-intensity exercise 32,33 . In addition to healthy young adults, there is emerging evidence that exercise can improve motor learning in clinical populations such as Parkinson's disease 34 , Huntington's disease 35 , or following a stroke 36 , however research into the bene ts of acute exercise for motor learning in healthy older adults is limited.…”
Section: Introductionmentioning
confidence: 99%